PENGGUNAAN BAP DAN KINETIN PADA INDUKSI TUNAS DARI PROTOCORM ANGGREK DENDROBIUM (Dendrobium Sp) PADA KULTUR IN VITRO - Meklin Bakar; Jeany Mandang; Deanne Kojoh; Sofia Demasabu (COCOS, 2016)
ABSTRACTThis research aims to understand the influence of the use of the dossier onBAP and Kinetin induction shoots from protocorm dendrobium orchid (dendrobium Sp)Conducted in the laboratory biotechnology Faculty Agriculture University SamratulangiManado for 4 months from from june until September 2015. The research uses randomdesign complete with treatment K(kontrol), B1( ms + 1 ppm ) dossier, B2( ms + 2 ppm )dossier, B3( ms + 3 ppm ) dossier, K1 (ms + 1 ppm kinetin ), K2 ( ms + 2 ppm kinetin ),K3 ( ms + 3 ppm kinetin ) and repeated as much as 3 times. Data analyzed by of varianceand continued with BNT 5% (test different real smallest).Treatment 3 ppm BAP had have real impact on higher plants and number of leaves. Thehighest plants that is 1.676 cm across get in treatment BAP 3 ppm while plants the lowestin BAP 2 ppm namely 0.500 cm. Number of leaves most found in BAP 3 ppm namely9.81 and number of leaves at least found in BAP 2 ppm namely 4.56, treatment BAP andKinetin has not been affecting the long the leaves of an orchid dendrobium.